2020
DOI: 10.3390/app10238365
|View full text |Cite
|
Sign up to set email alerts
|

Charging Platform of Chess-Pad Configuration for Unmanned Aerial Vehicle (UAV)

Abstract: The authors of this study designed and optimized a charging landing pad system that mitigates the landing accuracy issues of unmanned aerial vehicles (UAVs). The study looks at the charging process, energy conversion during periodic landing on a unique platform, and an onboard and on-ground scheme design procedure. The circuit is fixed on the UAV platform and comprises six integrated bridge rectifier diodes to alter the four connection pin terminals’ charge polarity. The inclusion of a current indicator shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…There are solutions that consist of a landing pad with no positioning systems and only wireless charging for the battery, such as [31][32][33][34][35]. It is a great way to keep a UAV charged if long routes should be crossed, but it can also be used to keep a UAV charged with no additional equipment needed on the docking station.…”
Section: Fixed Docking Stationmentioning
confidence: 99%
“…There are solutions that consist of a landing pad with no positioning systems and only wireless charging for the battery, such as [31][32][33][34][35]. It is a great way to keep a UAV charged if long routes should be crossed, but it can also be used to keep a UAV charged with no additional equipment needed on the docking station.…”
Section: Fixed Docking Stationmentioning
confidence: 99%
“…To overcome the issue, many researchers have devoted their time to focus on the autonomous charging approach to increase the endurance and the overall flight time as given in [11], [12]. As highlighted in [10], Silverman et al [13] demonstrated the autonomous recharging on a charging dock for a ground robot and researchers in [14] proposed a battery swapping station approach for small co-axial helicopters.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted in [10], Silverman et al [13] demonstrated the autonomous recharging on a charging dock for a ground robot and researchers in [14] proposed a battery swapping station approach for small co-axial helicopters. The recent work on contact-based technique can be found in [11] which is able to improve the misalignment issue and also the efficiency of the system. However, despite of many results available in the framework of contact-based autonomous charging approaches, every of the results suffer from their own conservatisms.…”
Section: Introductionmentioning
confidence: 99%